2013
DOI: 10.1038/nn.3337
|View full text |Cite
|
Sign up to set email alerts
|

Category-dependent and category-independent goal-value codes in human ventromedial prefrontal cortex

Abstract: To choose between manifestly distinct options, it is suggested that the brain assigns values to goals using a common currency. Although previous studies have reported activity in ventromedial prefrontal cortex (vmPFC) correlating with the value of different goal stimuli, it remains unclear whether such goal-value representations are independent of the associated stimulus categorization, as required by a common currency. Using multivoxel pattern analyses on functional magnetic resonance imaging (fMRI) data, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
172
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(201 citation statements)
references
References 60 publications
27
172
1
1
Order By: Relevance
“…However, it is negatively coupled with the lateral FP (FPl) cortex, ACC, and midinferior parietal lobule (IPL). A similar coupling pattern was seen when we took a coordinate from a food valuation task reported by McNamee et al (28). A coupling pattern very similar to this was found in the monkey on the medial gyrus rectus near area 14m, as defined by Mackey and Petrides (31).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…However, it is negatively coupled with the lateral FP (FPl) cortex, ACC, and midinferior parietal lobule (IPL). A similar coupling pattern was seen when we took a coordinate from a food valuation task reported by McNamee et al (28). A coupling pattern very similar to this was found in the monkey on the medial gyrus rectus near area 14m, as defined by Mackey and Petrides (31).…”
Section: Resultssupporting
confidence: 86%
“…factors affecting valuation, such as delay (27), indicating a "common currency" value representation. However, other studies have hinted at a posterior-to-anterior gradient of increasing abstractness in value representation (28). Here we show that this diversity of activity patterns is a consequence of the existence of several distinct component regions within the human vmPFC that can each be linked to different regions in the macaque.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Therefore, our finding cannot be explained by cognitive processes that merely reflect learned market prices. Further, in contrast to previous studies on commonscale representation of value (Levy and Glimcher, 2011;McNamee et al, 2013), we refrain from using any type of monetary valuation task. It is thus unlikely that the similarity of value signals we observe across different categories is artificially caused by a task that encourages subjects to evaluate items in a common reference frame, such as monetary value or a Likert scale.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the hypothesis of a common scale of subjective value, human functional magnetic resonance imaging (fMRI) studies have observed an overlap of value-related signals in the medial prefrontal cortex (mPFC) for different types of reward, such as consumer goods, monetary rewards, and also social rewards (Chib et al, 2009;FitzGerald et al, 2009;Lebreton et al, 2009;Smith et al, 2010;Kim et al, 2011;Levy and Glimcher, 2011;Lin et al, 2012). Further, it has been demonstrated that value signals for money and food options do not only spatially overlap, but that equally preferred money and food options elicit comparable BOLD responses in the mPFC both univariately (Levy and Glimcher, 2011) and multivariately (McNamee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%